2019
DOI: 10.1101/678391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precise Coordination of 3-dimensional Rotational Kinematics by Ventral Tegmental Area GABAergic Neurons

Abstract: The Ventral Tegmental Area (VTA) is a midbrain region implicated in a variety of motivated behaviors. However, the function of VTA GABAergic (Vgat+) neurons remains poorly understood. Here, using 3D motion capture, in vivo electrophysiology and calcium imaging, and optogenetics, we demonstrate a novel function of VTA Vgat+ neurons. We found 5 three distinct populations of neurons, each representing head angle about a principal axis of rotation: pitch, roll, and yaw. For each axis, opponent cell groups were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Instead, the effect of VTA DA neurons depends on the motivational context. This could explain why others have not been able to elicit movement by mimicking phasic DA activity [28]. This observation is in accord with the idea that DA, as a neuromodulator, primarily adjusts the gain of striatal medium spiny projection neurons [37].…”
Section: Articlesupporting
confidence: 64%
See 2 more Smart Citations
“…Instead, the effect of VTA DA neurons depends on the motivational context. This could explain why others have not been able to elicit movement by mimicking phasic DA activity [28]. This observation is in accord with the idea that DA, as a neuromodulator, primarily adjusts the gain of striatal medium spiny projection neurons [37].…”
Section: Articlesupporting
confidence: 64%
“…We next tested the effects of optogenetic inhibition on VTA DA neurons. We injected Cre-dependent soma-targeted Guillardia theta anion-conducting channelrhodopsin (stGtACR2), which has been shown to effectively shut down neural activity with high temporal precision [28][29][30], into the VTA of DAT-Ires-Cre (DAT::StGtACR2 VTA , n = 4) or of WT (WT::StGtACR2 VTA , n = 5) mice for controls (Figure 6G). We also confirmed potent optogenetic silencing of DAT::StGtACR2 VTA neurons using in vitro whole-cell patch-clamp recording in acutely prepared brain slices (Figures 6H and S6), demonstrating for the first time robust inhibition of DA neurons with this newly developed opsin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, we recently demonstrated that VTA GABA activation greatly attenuates reward seeking in an operant task heavily dependent on cue responding, while chemogenetic activation of the VTA GABA terminals in the NAc had no effect [34]. Other studies have shown that VTA GABA activation promotes sleep [35] and head orienting towards desired spatial targets [36]. Thus, it is becoming clear that VTA GABA neurons contribute to the regulation and control of a myriad of motivated behaviors.…”
Section: Introductionmentioning
confidence: 90%